3D Printed Embolization Module for Treatment Training of Chronic Subdural Hematomas in Interventional Neuroradiology (Transactions on Additive Manufacturing Meets Medicine, 2025)
Minimally invasive techniques have revolutionized the treatment of cerebrovascular disease, including middle meningeal artery embolization (MMAE) as a promising alternative to open surgical treatment of chronic subdural hematoma (cSDH). However, training in MMAE still requires the use of animal models, which have ethical concerns and are not anatomically realistic. This study presents the development of a 3D printed, interchangeable MMA embolization module for integration into the HANNES neurointerventional simulator with the previously developed MMA model to enable realistic simulation of cSDH treatment with the liquid embolic agent Onyx. The module was designed in a patient-like geometry and manufactured using stereolithography (SLA) printing with two different materials. A detailed evaluation of the manufacturing parameters showed that the choice of material and print orientation had a significant impact on post-processing efficiency. The final module was tested in a realistic angiography suite with original treatment instruments and its performance was evaluated by experienced neuroradiologists. The module received high marks for anatomical realism, flow characteristics and embolic agent distribution. The results highlight the potential of the module as an effective tool for neurointerventional training, reducing the need for animal models while providing a standardized, reproducible training platform. Future work could focus on integrating the module into structured training courses, exploring its application for radiation-free learning due to its transparency, and incorporating objective evaluation metrics to assess procedural performance and skill acquisition.
Keywords: HANNES; additive manufacturing; Neurointerventional Training; subdural hematoma; Embolization